Impact of Testing Method on Measured Flexural Strength of Model-Scale Ice - Petry, Alice; Suominen, Mikko; Matala, Riikka; Skogström, Toni; Seppänen, Eetu (2023)
Ice-going vessels and offshore structures designed to break ice in bending rely on the reported flexural strength of ice. Depending on the ice conditions, the flexural strength can be affected by the choice of testing method. Nonetheless, the International Towing Tank Committee (ITTC) recommends three different methods to determine the flexural strength of model ice. To address the uncertainty related to the choice of testing method, this study performs downward and upward cantilever beam tests and in-situ and ex-situ three-point bending tests in ethanol-doped and saline fine-grained model ice, respectively. Experiments were performed at the Aalto University Ice and Wave Tank and in the ice basin of Aker Arctic Technology using the same test setup. The results show that the flexural strength of both types of model ice is influenced by bending direction of the ice samples. The testing method has only a minor effect on the determined flexural strength. Consequently, the testing guidelines proposed by the ITTC sufficiently address the uncertainty in the flexural strength of ethanol-doped and of saline fine-grained model ice. Peer reviewed